DAMPAK SERTIFIKASI DAN LABELISASI HALAL TERHADAP PENJUALAN MIE SAMYANG MENURUT UNDANG-UNDANG JAMINAN PRODUK HALAL - Lananda, Ardelia; Megawati, Leny (The Juris, 2025)
Certification and labeling are two different processes, but they are interrelated. Halal certification is a verification process to obtain recognition from an official institution, while a halal label is a symbol that is included on the product packaging as proof that the product has obtained halal certification. The implementation of halal certification and labeling in the food industry in Indonesia is an obligation that must be complied with by every business actor. This is stated in Law Number 33 of 2014 concerning Halal Product Assurance. The purpose of this study is to analyze in more depth the Implementation of Halal Certification Submission Regulations on Samyang Noodle Products and to identify the Influence of Halal Certification and Labeling on Consumer Trust in Selling Samyang Noodles According to the Halal Product Assurance Law. The method used in this study is the normative legal research method. This research method is carried out by examining problems and processing data obtained from legal regulations in accordance with existing regulations and rules or norms as the basis for research. The results of the study indicate that the implementation of halal certification and labeling has a significant impact on the sale of Samyang noodle products. Before obtaining halal certification and labeling, Samyang noodle products experienced a 30% decline in demand due to concerns among Muslims regarding their halal status. However, after obtaining halal certification and labeling from the Indonesian Ulema Council (MUI), sales of Samyang noodle products increased again due to legal certainty and consumer trust.